2008
DOI: 10.1097/ss.0b013e3181893b59
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Organic Phosphorus With Clays Extracted From Oxisols

Abstract: In highly weathered soils, such as tropical soils, organic phosphorus (P) may decline together with total P and could be represented by a relatively lower amount of inositol phosphates compared with temperate soils. The aim of this work was to understand the abiotic processes leading to inositol phosphate retention in highly weathered soils. Sorption of myo-inositol hexakisphosphate and inorganic phosphate (Pi) on two clay fractions (A and B) extracted from Brazilian oxisols was studied, examining both the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 47 publications
(74 reference statements)
2
33
1
5
Order By: Relevance
“…Several studies have reported correlations between IP 6 and amorphous metal oxides in acidic soils (Anderson et al, 1974;Giaveno et al, 2008;McKercher and Anderson, 1968;Turner et al, 2003). In addition, IP 6 concentrations have been shown to fluctuate in parallel with changes in amorphous Al and Fe hydroxides during long-term pedogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported correlations between IP 6 and amorphous metal oxides in acidic soils (Anderson et al, 1974;Giaveno et al, 2008;McKercher and Anderson, 1968;Turner et al, 2003). In addition, IP 6 concentrations have been shown to fluctuate in parallel with changes in amorphous Al and Fe hydroxides during long-term pedogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…), leading to their stabilization and protection from biological attack (Celi and Barberis 2007). However, there is evidence that inositol hexakisphosphate interacts relatively weakly with clay surfaces in strongly-weathered soils, due to a reduction in the number of phosphate groups involved in its stabilization on crystalline mineral surfaces (Giaveno et al 2008). Indeed, studies of soil chronosequences in New Zealand indicated that inositol phosphate concentrations decline in old, strongly-weathered soils in parallel with a reduction in the concentration of amorphous metal oxides (McDowell et al 2007;Turner et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Os valores de PCZ encontrados neste trabalho para o LVdf e gibbsita corroboram aqueles propostos para materiais ricos em óxidos de ferro e de alumínio, que variam entre 7,8 e 9,5. 7 Giaveno et al 21 avaliaram o potencial zeta de hematita e gibbsita sintéticas e da fração argila de dois Latossolos do Mato Grosso do Sul sob diferentes ambientes, Cerrado nativo e pastagem. Para hematita, o potencial zeta variou de +30 mV em pH próximo de 3,0 até -20 mV em pH 11,0, alcançando o PCZ em pH 7,0.…”
Section: Resultados E Discussão Efeito Da Vinhaça Da Adsorção De P Eunclassified
“…34 A adsorção de fósforo afetou o potencial zeta da fração argila dos solos (Figura 1), corroborando estudos prévios, nos quais se verificou que a adsorção específica do ânion fosfato torna a superfí-cie carregada mais negativamente e também reduz o PCZ. 16,17,20,21 A adsorção de P tornou a superfície da fração argila de ambos os solos mais eletronegativa e reduziu seu PCZ, sendo essas alterações mais pronunciadas quando as amostras foram previamente tratadas com vinhaça. Para o LVdf, sem vinhaça, na menor concentração inicial de P (0,08 mM), observa-se uma redução do potencial zeta, alcançando o PCZ em 3,6 e apresentando uma carga líquida negativa acima desse valor.…”
Section: Resultados E Discussão Efeito Da Vinhaça Da Adsorção De P Eunclassified
See 1 more Smart Citation